Histological study of the talon and glandular sac annex of Megalobulimus (Gastropoda, Strophocheilidae) - Temoche, Haydee (2024)
In this study, the histology of the talon and the annex glandular sac (AGS) of the reproductive system from five species of Megalobulimus (Gastropoda, Stylommatophora, Strophocheilidae) is described. Hematoxylin-Eosin staining technique was used. It was found that the talon is a compact muscular structure housing the fertilization pouch, a tubular structure lined by folded ciliated cylindrical epithelium, to whose proximal end the hermaphroditic duct connects. This duct terminates in the fertilization chamber, from which the spermathecal tubules originate. These tubules branch out to their blind ends and store exogenous sperm. In the tubules, spermatozoa were observed, mostly with their heads attached to the ciliated epithelial cells and their tails free in the lumen. The wall of the AGS has an outer layer of smooth muscle and, lining the lumen, a non-ciliated glandular columnar epithelium with various degrees of folding and subepithelial mucous cells. The secretions from these cells flow into the collecting duct near the base of the talon. Far from the albumen gland, a similar substance was observed along with exogenous sperm in the spermathecal tubules. Differences between species were identified, with the most significant and phylogenetically relevant feature being the differentiation of the talon, which was more pronounced in M. capillaceus compared to the other four species studied (M. popelairianus, M. carrikeri, M. leucostoma, and M. maximus).